A low-cost and portable active noise control unit - Wang, Zhaohan (Nanyang Technological University, 2022)
The aim of the project is to apply state-of-the-art active noise control techniques to reduce noises generated by electrical appliances like coffee machine. The algorithm applied is the modified FXLMS algorithm, which produces anti-noise wave based on the measurements of the reference microphone and the error microphone, and an outcome of zero residual noise is expected. The challenge is that the experiment takes place under open space condition, where a typical active noise control system operates in an enclosed area, such as a closed room or relatively closed area such as volume inside earphones. A test bench is set up for validating, where Sigma Studio software is utilized to control the whole system and ADAU1452 is the digital signal processor selected. In this report, various Active Noise Control systems and algorithms are introduced, then, simulations of typical algorithms are carried out. Finally, details on implementing experiments are presented followed by possible future works.